FPGA implementation on secure parking system - Mohd Khairul Akli Ab Ghani (Universiti Malaysia Perlis, 2008)
Secure parking system is a project which could give a comfort to the users for safety parking their cars especially at the apartment and condominium areas. This idea acquired after intensive observation have been made based on the security system at many parking places. Besides that, with this system each owners need not to worry to find parking places because of after entering a correct pass code, then a gate will be opened and light the lamp indicator. Hence, it will show where the users should park their cars. Quartus II software has been adopted in this project as well as Altera UP-2 Board as the hardware. This project has been divided into two main phases; software development and hardware development. In the software development, it’s involved the design entry, simulation process as well as synthesis process. Meanwhile, in the hardware development has involved in constructing the detector circuit and the analog to digital converter circuit. The results of this project have shown working properly on Altera UP-2 Board.